Réponses

  • Utilisateur Brainly
2014-03-08T16:30:57+01:00
Résolution de l'inéquation:

(2x+3) (-4x+4) ≤ 9 -4x²
(2x+3) (-4x+4) ≤ (3-2x) (3+2x)
(2x+3) (-4x+4) - (3-2x) (3+2x) ≤0
(2x+3) (-4x+4 - 3 +2x) ≤0
(2x+3) (-2x+1) ≤0

On dresse un tableau de signes:

x             - ∞          -3/2          1/2               + ∞
2x+3                -       0       +                +
-2x+1              +                +    0          -
E                     -        0       +    0          -

S= ) -∞ ; -3/2 )   U  (1/2 ; +∞ (

Voilà! J'espère t'avoir aidé ! :)